Penggunaan Gaya Bahasa pada Akun Instagram @Travellingsumut dalam Mempromosikan Destinasi Wisata di Sumatera Utara - Tri Pertiwi (Lembaga Pengembangan Kinerja Dosen, 2024)
The purposes of this study are to find out the types of language style and explain the meaning of them which are used in promoting tourism objects of North Sumatera by the instagram account of @travellingsumut. The method used in this research was descriptive qualitative method. The data of this research was the captions which are posted by the instagram account of @travellingsumut in promoting tourism objects of North Sumatera. Based on the analysis data, there was found two kinds of language styles in promoting tourism objects of North Sumatera. The two types of language style are comparative language style/figure of speech with 23 sentences and affirmative language style/figure of speech with 2 sentences. In comparative language/figure of speech styles, four types of figures of speech were found, namely personification, metaphor, hyperbole and simile. In the language style/figure of speech of affirmation, one type of language style is found, namely repetition. Based on these findings, it can be concluded that the language styles that used by the instagram account of @travellingsumut in promoting tourism objects of North Sumatera have function to persuade people to visit North Sumatera and enjoy the natural beauty and tourism objects in there.